(untitled) (TROPICAL WETLAND JOURNAL, 2023)
The aim of this research is to investigate the effect of chicken manure compost and agricultural lime on the growth media used for floating system chili cultivation. The study involved the application of 500 g of chicken manure compost and 6 g of agricultural lime to each floating medium. Chili plants were chosen as the subject for observation of their growth and yield. Based on descriptive data analysis, it was found that the application of 500 g of chicken manure compost per planting hole was able to improve the observed chemical parameters, namely pH and available nitrogen (NH4+, NO3-).